INTEGRATIVE EXERCISE AND DIDACTIC GAMES AS A MEANS OF DEVELOPING LEADERSHIP SKILLS IN PRESCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2025)
The article presents some thoughts on the specifics of integrative exercises and didactic games in developing the leadership skills of preschool children and their content. The article also presents some thoughts on the role of integrative exercises and didactic games in preschool education, their role in the development of preschool children.